Herbarium as a genre of former scientific discourse in contemporary manifestations - Rejter, Artur (Papers in Linguistics, 2023)
The article deals with contemporary realizations of a herbarium, a classic genre of old scientific discourse. The concept clearly present in Polish linguistic genology referring to three types of genre patterns was used: 1) canonical pattern, 2) alternative pattern, 3) adaptive pattern. Within each type of genre pattern, individual aspects of the pattern were observed: structural, stylistic, pragmatic, and cognitive (semantic). The concept of different genre patterns referred to the prototypical form (referring to old scientific discourse) enabled the indication of various manifestations of the herbarium’s long-lasting presence in the communication universe. This genre, which was proper for scientific discourse in its initial stage of functioning in past epochs, today finds various – sometimes related, but often completely different – and sometimes surprising and very creative – updates. This allows us to put forward a thesis about multidirectional and complex forms of discourse transformations, their interpenetration, and mutual references. The proposed considerations also seem to confirm the validity of research on speech genres in the context of discourse transformations.